2009
DOI: 10.1016/j.cub.2009.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Human Perceptual Learning by Mental Imagery

Abstract: Perceptual learning is learning to perceive. For example, a radiologist is able to easily identify anomalies in medical images only after extended training. Theoretical and psychophysical studies [1-12] suggest that such improvements of performance are accomplished by neural synaptic changes driven by the repetitive presentation of stimuli. Here, we demonstrate that an equally reliable improvement can also occur in the absence of physical stimulation. Imagining the crucial part of a bisection stimulus was suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 36 publications
5
79
1
2
Order By: Relevance
“…Recent behavioural and neural imaging research suggests that imagery can be studied objectively (kosslyn et al, 2001;Naselaris, Olman, Stansbury, Ugurbil, & Gallant, 2015;Pearson, Clifford, & Tong, 2008;Pearson, Rademaker, & Tong, 2011;Stokes, Thompson, Cusack, & Duncan, 2009;Tartaglia, Bamert, Mast, & Herzog, 2009). Pearson, Clifford, and Tong (2008) developed an objective measure for assessing visual mental imagery strength, utilising brief presentations of binocular rivalry, a sensory phenomenon in which each eye is presented with a different pattern, causing them to compete for perceptual dominance (Blake & Logothetis, 2002;Pearson & Brascamp, 2008).…”
Section: Methodsmentioning
confidence: 98%
“…Recent behavioural and neural imaging research suggests that imagery can be studied objectively (kosslyn et al, 2001;Naselaris, Olman, Stansbury, Ugurbil, & Gallant, 2015;Pearson, Clifford, & Tong, 2008;Pearson, Rademaker, & Tong, 2011;Stokes, Thompson, Cusack, & Duncan, 2009;Tartaglia, Bamert, Mast, & Herzog, 2009). Pearson, Clifford, and Tong (2008) developed an objective measure for assessing visual mental imagery strength, utilising brief presentations of binocular rivalry, a sensory phenomenon in which each eye is presented with a different pattern, causing them to compete for perceptual dominance (Blake & Logothetis, 2002;Pearson & Brascamp, 2008).…”
Section: Methodsmentioning
confidence: 98%
“…Thus any factor that could modulate the relative contributions of the two opponent attentional mechanisms may have influence on the PL specificity/generalization. Specifically, different training (e.g., training time: long-term or short-term; training method: interleaved/roving training or adaptive/regular training; task load during training: easy or difficult) and testing procedures (e.g., the nature of the interested stimulus features; exposure/testing time before/during test; task load during test) may be important factors at least partly explaining why some studies showed strong behavioral specificity (e.g., Hung & Seitz, 2014;Karni & Sagi, 1991) whereas others did not (e.g., Harris, Gliksberg, & Sagi, 2012;Liu & Weinshall, 2000;Tartaglia et al, 2009;Zhang et al, 2010).…”
Section: Factors Which May Influence the Specificity And Generalizatimentioning
confidence: 98%
“…In many PL models, the stimulus-specificity of PL is attributed to the primary visual cortex (i.e., area V1) where neurons are highly selective for stimulus location and orientation (e.g., Adini, Sagi, & Tsodyks, 2002;Teich & Qian, 2010;Zhaoping, Herzog, & Dayan, 2003). However, some studies found such behavioral stimulus specificity can be eliminated under certain conditions, showing strong transfer of PL effects (Aberg, Tartaglia, & Herzog, 2009;Ahissar & Hochstein, 1997;Harris, Gliksberg, & Sagi, 2012;Hussain, Bennett, & Sekuler, 2012;Liu & Weinshall, 2000;Tartaglia et al, 2009;Xiao et al, 2008). Moreover, some behavioral studies showed task-specificity of PL in which the PL effect cannot transfer from the trained task to another task involving the same or similar stimuli (Ahissar & Hochstein, 1993;Huang et al, 2007;Shiu & Pashler, 1992), though others found successful transfer of learning across tasks (Chung, Legge, & Cheung, 2004;Green & Bavelier, 2003;Leonards et al, 2002;Nazir et al, 2004;Yu, Klein, & Levi, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…[5][6][7][8] It has been shown to improve perceptual learning on visual tasks such as spatial discrimination and contrast detection. 9 In surgery, MI as a technique of motor learning and practice has the theoretical advantages of being safe and inexpensive when compared with traditional learning in the operating theatre or in a simulation environment. 1 In addition, it has been shown to improve nontechnical aspects of surgical performance such as stress 10 and confidence.…”
Section: Introductionmentioning
confidence: 99%